Pelatihan KPPS Pilkada 2024: Tingkatkan Kompetensi dan Efektivitas Penyelenggaraan Pemilu - Nurmidin, M Fadhel (-, 2025)
The Indonesian election presents significant technical and non-technical challenges for Polling Station Working Groups (KPPS), such as lack of regulatory understanding, conflicts at polling stations, and inefficient time management. This study aims to enhance KPPS competence through technical guidance, including training on electoral regulations, technical procedures, conflict resolution, and result reporting. Evaluation revealed a significant improvement in participants' understanding, with average pre-test scores rising from 64.2 to 88.5 in the post-test. These findings demonstrate the effectiveness of technical guidance in preparing KPPS to address electoral challenges.